Is artificial intelligence for everyone? Analyzing the role of ChatGPT as a writing assistant for medical students - Shahsavar, Zahra; Kafipour, Reza; Khojasteh, Laleh; Pakdel, Farhad (Frontiers in Education, 2024)
This study explores the potential impact of ChatGPT on the academic writing skills development of medical students enrolled in a compulsory 3-unit writing course at a medical university. The research focuses on two primary objectives, which are formulated as two research questions: Firstly, does the use of ChatGPT enhance medical students’ English academic writing skills compared to conventional writing training? Secondly, how does the use of ChatGPT impact on different components of academic writing? A longitudinal intervention design was employed with 83 participants from two writing classes in the experimental and control groups. The findings demonstrated ChatGPT’s significant impact on enhancing medical students’ English academic writing skills, with large effect sizes. ChatGPT enhanced students’ writing skills, especially content, organization, vocabulary, and mechanics in the experimental group, while its impact on language use is limited. AI tools like ChatGPT can be valuable in assisting with certain aspects of writing, but they should not be considered a one-size-fits-all solution for enhancing writing skills. The result of the study can be beneficial for educators, particularly those interested in teaching writing.